The Relationship between Family Attitudes and Complementary Feeding (MP-ASI) for Infants at Lubuk Alung Health Center in 2023 - Tyas, Dina; Sa'danoer, Ira; Silvia, Elwitri (Institute Of Computer Science (IOCS), 2024)
Giving MP-ASI to infants is food or drink as a complement to breast milk given to infants, Based on research conducted in Indonesia from 2018-2020 shows data that more than 40% of infants aged 0-6 months are exclusively breastfed, while the other 60% have received MP-ASI when the baby is less than 6 months old. In 2020, around 1.5 million babies lost their lives due to improper feeding. The purpose of this study was to determine the attitude of families with complementary feeding (MP-ASI) for infants at the Lubuk Alung Health Center in 2023. This research uses quantitative methods with Analytical Design with a cross sectional approach. The population in this study was 1,022 all mothers who had babies at the Lubuk Alung Health Center, with a sample of 91 respondents. By sampling using the Random Sampling technique. Data was collected using questionnaires, data processing using the SPSS program using the chi square test. The results of statistical tests were found not to give MP-ASI to infants, namely 54 people (59.3%), respondents had a less attitude in giving MP-ASI, which was 58 people (63.7%). There is a relationship between family attitudes and complementary feeding (MP-ASI) for infants at the Lubuk Alung Health Center. Conducted with a chi square test with a p-value of 0.00. The conclusion in this study is the family's attitude by giving MP-ASI at the Lubuk Alung Health Center in 2023 so that the baby's family or mother, provides MP-ASI to babies at the age of >6 months so that indigestion does not occur in infants.